Dǝrsan des Yaʿqob von Sǝrug für den vierten Sonntag im Monat Taḫśaś - Uhlig, Siegbert (Aethiopica, 1999)
Yaʿqob of Sǝrug, one of the most important Syrian church writers of the 6th century, wrote more than 750 metrical works. Many of them are translated into Arabic, and this version was the Vorlage for the Ethiopian translator. About 20 of Yaʿqob’s homilies are representes in the the Ethiopic tradition, and most of them deal with christological-mariological themes. The Dǝrsan for the fourth Sunday of Taḫśaś is edited and translatedd on the basis of six Gǝʿǝz manuscripts. The contents concern the annunciation of the incarnation to the Virgin Mary.